Analisis Kompetensi Profesional Guru Melalui Penggunaan Media Pembelajaran Berbasis Information Technology - Lutfiana, Rose Fitria (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2021)
The purpose of this research is to analyze learning media that utilize information technology in order to improve professional competence at SMP Muhammadiyah 8 Batu. The approach used is qualitative and the type of research is descriptive. The research location was at SMP Muhammadiyah 8 Batu for three months, namely August - November 2020. The informants included the principal and all teachers at SMP Muhammadiyah 8 Batu. The data collection process used includes documentation study, interview and observation. For the data analysis process chosen was the Milles Huberman analysis technique which consisted of four stages, namely data collection, data reduction, data presentation and conclusions. The results obtained are: (a) teachers are able to manage information technology-based learning such as edmodo, office 365, google classroom, and WAG; and (b) the teacher is able to design various information technology-based learning media used in learning such as making instructional videos, making quizzes with the quizzes and PPT applications.